2000
DOI: 10.1086/314032
|View full text |Cite
|
Sign up to set email alerts
|

Deaths of Children during an Outbreak of Hand, Foot, and Mouth Disease in Sarawak, Malaysia: Clinical and Pathological Characteristics of the Disease

Abstract: From April through June 1997, 29 previously healthy children aged <6 years (median, 1.5 years) in Sarawak, Malaysia, died of rapidly progressive cardiorespiratory failure during an outbreak of hand, foot, and mouth disease caused primarily by enterovirus 71 (EV71). The case children were hospitalized after a short illness (median duration, 2 days) that usually included fever (in 100% of case children), oral ulcers (66%), and extremity rashes (62%). The illness rapidly progressed to include seizures (28%), flac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
385
3
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(413 citation statements)
references
References 37 publications
21
385
3
4
Order By: Relevance
“…In these aspects, this outbreak is similar to those that occurred in Malaysia and Taiwan in recent years (6,7,9,10).…”
Section: Discussionsupporting
confidence: 79%
“…In these aspects, this outbreak is similar to those that occurred in Malaysia and Taiwan in recent years (6,7,9,10).…”
Section: Discussionsupporting
confidence: 79%
“…6,26,27 These symptoms suggest the presence of lesions in the CNS of the monkeys. In this study, physical examination of the monkeys that were infected via these four routes revealed that the muscle tension in the limbs was in the normal range, and no herpes-like skin lesions were observed on the hands, feet or mouths.…”
Section: Clinical Manifestations Of Ev71 Infection In Rhesus Monkeys mentioning
confidence: 99%
“…Neurological cases with a high case fatality rate were first recorded in Bulgaria in 1975, where they were mainly associated with poliomyelitis-like paralysis, and in Hungary in 1978 (Chumakov et al, 1979;Nagy et al, 1982). The recent outbreaks in Asia were also associated with a high incidence of neurotropic complications (Chan et al, 2000); a case fatality rate of 0.6 % was noted during the outbreaks in 2008 (Huang et al, 2009). Fatal cases in children under 5 years of age were mainly associated with neurogenic pulmonary oedema (Chinese Center for Disease Control and Prevention and the World Health Organization, 2008; Ho et al, 1999).…”
Section: Introductionmentioning
confidence: 99%